Neonatal Intracranial Aneurysm Rupture Treated by Endovascular Management: A Case Report - Yi-Pei Tai; I-Ching Chou; Ming-Shiang Yang; Hung-Chih Lin; Hsiao-Yu Chiu; Huang-Tsung Kuo; Bai-Horng Su; Chang-Hai Tsai (Pediatrics and Neonatology)
Pediatric intracranial aneurysm rupture is rare, and is traditionally managed by surgical clipping. To the best of our knowledge, endovascular embolization of aneurysms in neonates has not previously been reported in Taiwan. We report a 9-day-old boy with intracranial aneurysms who underwent endovascular embolization, representing the youngest reported case in Taiwan. The 9-day-old boy presented with non-specific symptoms of irritable crying, seizure and respiratory distress. Computed tomography disclosed intraventricular hemorrhage, subarachnoid hemorrhage and focal intracranial hemorrhage around the right cerebellum. Subsequent computed tomographic angiography showed two sequential fusiform aneurysms, measuring 3 mm, located in the right side posterior inferior cerebellar artery (PICA). The patient underwent endovascular embolization because of the high risk of aneurysm re-rupture and the impossibility of surgical clipping due to the fusiform nature of the aneurysms. A postembolization angiogram revealed complete obliteration of the right distal PICA and proximal aneurysm. The distal PICA aneurysm was revascularized from the collateral circulation, but demonstrated a slow and delayed filling pattern. The patient's condition remained stable over the following week, and he was discharged without anticonvulsant therapy. No significant developmental delay was noted at follow-up at when he was 3 months old. This case emphasizes the need for clinical practitioners to consider a diagnosis of intracranial hemorrhage in neonates with seizure and increased intracranial pressure. Neonatal intracranial aneurysms can be treated safely by endovascular treatment.